Teaching Arabic To Non-Native Speakers: Interests and Challenges/ تعليم اللُّغة العربيَّة للنّاطقين بغيرها: الاهتمام والتَّحديات - Ibrahim, Islam Mahmoud; Rouyan, Nurazan Mohmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The research discusses teaching Arabic to non-native speakers, in terms of the factors of global interest in Arabic as a second language in the modern era and the reasons for this. It also discusses the most prominent challenges facing specialists in teaching Arabic to non-native speakers when preparing educational material for non-native learners. It also highlights the suffering and hardship experienced by specialists in this field in preparing material to facilitate its teaching to learners. This research investigates the key factors driving the growing global interest in learning Arabic as a second language in the modern era, while also exploring the primary challenges and obstacles that specialists encounter in teaching Arabic to non-native speakers. The research relied on published books, studies, and research that discussed this topic. The research concluded that the global interest in Arabic as a second language is primarily driven by geopolitical and economic factors, media and cultural production influence, and a growing recognition of its strategic importance in international communications. Furthermore, the study documented the considerable challenges and meticulous effort specialists invest in developing Pedagogically Effective scientific material tailored for non-native speakers.